Analisis Sambungan Proses Underwater Friction Stir Welding Pada Alumunium Seri 6005-T6 Terhadap Kuat Impact dan Struktur Micro - Prasetya, Fikri; Mulyadi; Firdaus, Rachmat (Indonesian Journal Publisher, 2025)
Underwater Friction Stir Welding (UFSW) is a solid state welding process that is able to unite materials with water that are relatively difficult to weld using fusion welding. Additionally, this process is very energy efficient and friendly compared to fusion welding. While there are several advantages of UFSW over fusion welding, the thermal cycling involved in UFSW can cause softening of the joint, especially in Heat Treatable Aluminum Alloys (HTTA), in this case the material AA6005-T6. This is caused by the dissolution or acidification of reinforcing deposits during the welding process, which ultimately results in a decrease in the mechanical properties of the joint. UFSW can be the process of choice to overcome these limitations. This process is suitable for alloys that are sensitive to heating during welding and is widely used for HTTA. The aim of this article is to provide a comprehensive literature review regarding the current status and development of UFSW and its importance compared to WPS with the aim of discussing and summarizing various aspects of UFSW. Special attention is paid to basic principles including material flow, generation temperature, process parameters, microstructure and mechanical properties. The research results showed that the highest impact value in specimen 2 was 0.944 Joules/mm2 compared to the base metal with an impact value of 0.641 Joules/mm². Micro tests on fine grains in the weld nugget (WN) area clearly show differences with a denser structure compared to the thermo-mechanically affected zone (TMAZ) which is the tool edge area or what is usually called plastic deformation in the UFSW process, which can cause zones the weld becomes stronger than in the base metal (BM) area.